Music induces different cardiac autonomic arousal effects in young and older persons - Hilz, Max-Josef; Stadler, Peter; Gryc, Thomas; Nath, Juliane; Habib-Romstoeck, Leila; Stemper, Brigitte; Buechner, Susanne; Wong, Samuel; Koehn, Julia (Autonomic Neuroscience-Basic & Clinical, 2014)
Autonomic arousal-responses to emotional stimuli change with age. Age-dependent autonomic responses to music-onset are undetermined.To determine whether cardiovascular-autonomic responses to "relaxing" or "aggressive" music differ between young and older healthy listeners.In ten young (22.8±1.7 years) and 10 older volunteers (61.7±7.7 years), we monitored respiration (RESP), RR-intervals (RRI), and systolic and diastolic blood pressure (BPsys, BPdia) during silence and 180second presentations of two "relaxing" and two "aggressive" classical-music excerpts. Between both groups, we compared RESP, RRI, BPs, spectral-powers of mainly sympathetic low-frequency (LF: 0.04-0.15Hz) and parasympathetic high-frequency (HF: 0.15-0.5Hz) RRI-oscillations, RRI-LF/HF-ratios, RRI-total-powers (TP-RRI), and BP-LF-powers during 30s of silence, 30s of music-onset, and the remaining 150s of music presentation (analysis-of-variance and post-hoc analysis; significance: p<0.05).During silence, both groups had similar RRI, LF/HF-ratios and LF-BPs; RESP, LF-RRI, HF-RRI, and TP-RRI were lower, but BPs were higher in older than younger participants. During music-onset, "relaxing" music decreased RRI in older and increased BPsys in younger participants, while "aggressive" music decreased RRI and increased BPsys, LF-RRI, LF/HF-ratios, and TP-RRI in older, but increased BPsys and RESP and decreased HF-RRI and TP-RRI in younger participants. Signals did not differ between groups during the last 150s of music presentation.During silence, autonomic modulation was lower - but showed sympathetic predominance - in older than younger persons. Responses to music-onset, particularly "aggressive" music, reflect more of an arousal- than an emotional-response to music valence, with age-specific shifts of sympathetic-parasympathetic balance mediated by parasympathetic withdrawal in younger and by sympathetic activation in older participants.
EVALuna2:22324